Limiting Injury During Saphenous Vein Graft Preparation For Coronary Arterial Bypass Prevents Metabolic Decompensation. Issue 1 (December 2017) - Cheung-Flynn, Joyce; Song, Jun; Voskresensky, Igor; Wise, Eric; Liu, Yapu; Xiong, Yanhua; Eagle, Susan; Brophy, Colleen; Flynn, C.
Abstract Standard harvest and preparation of human saphenous vein (HSV) for autologous coronary and peripheral arterial bypass procedures is associated with injury and increased oxidative stress that negatively affect graft performance. In this study we investigated the global metabolomic profiles of HSV before (unprepared; UP) and after standard vein graft preparation (AP). AP-HSV showed impaired vasomotor function that was associated with increased oxidative stress, phospholipid hydrolysis and energy depletion that are characteristic of mechanical and chemical injury. A porcine model (PSV) was utilized to validate these metabolomic changes in HSV and to determine the efficacy of an improved preparation technique (OP) using pressure-regulated distension, a non-toxic vein marker, and graft storage in buffered PlasmaLyte solution in limiting metabolic decompensation due to graft preparation. Deficits in vasomotor function and metabolic signature observed in AP-PSV could be largely mitigated with the OP procedure. These findings suggest that simple strategies aimed at reducing injury during graft harvest and preparation represents a straightforward and viable strategy to preserve conduit function and possibly improve graft patency.